Development of UK recommendations on treatment for post‐surgical erectile dysfunction. Issue 5 (4th November 2013) - Kirby, M. G.; White, I. D.; Butcher, J.; Challacombe, B.; Coe, J.; Grover, L.; Hegarty, P.; Jackson, G.; Lowndes, A.; Payne, H.; Rees, J.; Sangar, V.; et al.
Summary Aim To develop a management strategy (rehabilitation programme) for postsurgical erectile dysfunction (ED) among men experiencing ED associated with treatment of prostate, bladder or rectal cancer that is suitable for use in a UK NHS healthcare context. Methods PubMed literature searches of ED management together with a survey of 13 experts in the management of ED from across the UK were conducted. Results Data from 37 articles and completed questionnaires were collated. The results discussed in this study demonstrate improved objective and subjective clinical outcomes for physical parameters, sexual satisfaction, and rates of both spontaneous erections and those associated with ED treatment strategies. Conclusion Based on the literature and survey analysis, recommendations are proposed for the standardisation of management strategies employed for postsurgical ED.